(3eSGFd eJaQbIs - (3CHh GdbGSe, GdTQja GdeQJVj, Ydj Hf GdMSjf Hf ehSi, J (B436(3g` (B1044(3e(B)s ((3cGTa GdZWGAs)
(3ChdgG (B:s
(3ChdgG(B: (3eSCdI GdTjYI GdEeGejI, eWHbI Ydi EfcGQ GdeSM Ydi GdNajf hgj YfOfG GdaQbI GdeMbI, eSFdI NQLJ aj eMQe SfIs
(3BNQgG (B:s
(3BNQgG(B: (3aCeG GdeJecf ef GdEYQGH aEf dMf HZjQ YeO aVdhfg LGFRI hEf JYeO GddMf aGdChdi Cf UdGJg aGSOI hef CaJi ef CUMGHfG HNdGag cGf ZjQ eUjHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L(B4: 278s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3abg GdePGgH GdCNQis